Exploring Tourist Motivations in the Glamping Experience: A Qualitative Study in Kintamani: . - Marina, Marina; Karina Ega Nirwana; Kanom, Kanom; Tri Retno Nugroho (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Glamping (glamorous camping) has emerged as a contemporary form of accommodation that combines the essence of outdoor camping with the comfort of modern facilities, offering tourists a distinctive experience of being close to nature without sacrificing luxury. In Indonesia, particularly in Kintamani, Bali, glamping has grown rapidly in line with increasing interest in nature-based tourism and unique travel experiences. Despite its popularity, studies that specifically address tourist motivation in the glamping context remain limited. This research aims to explore the motivations that drive tourists to choose the glamping experience in Kintamani through a qualitative approach. Data were collected using in-depth interviews, participatory observation, and documentation with tourists who had experienced glamping in Kintamani. Thematic analysis revealed two main categories of motivation: intrinsic and extrinsic. Intrinsic motivations include the desire to gain positive feelings, escape from daily routines, seek novelty, strengthen social relationships, and enhance social status. Extrinsic motivations are shaped by external factors such as natural beauty, promotional offers, invitations from friends or family, social media needs, and lifestyle trends. The findings highlight that glamping in Kintamani is not only perceived as an alternative form of accommodation but also as a lifestyle-driven tourism experience that blends personal well-being, social expression, and natural immersion. These insights contribute to a deeper understanding of tourist behavior in experiential tourism and provide implications for glamping providers and destination managers to design more relevant and sustainable tourism strategies.